Cakupan imunisasi tetanus toxoid ibu hamil di daerah terpencil - M.Lukman Arsyad (Berita Kedokteran Masyarakat (BKM), 2006)
Background: The aim of this study to measures describe community health status in regencies levels to get Indonesian Health in 2010 year, community health status can be got through add health services facilities, materials and medicine beside manpower of health professional to coverage for all community especially community in remote area and poor, then they can be access to basic health services quickly, right, easy and cheap. This study had started from 2003 until the end 2004 in Mamuju Regencies as a remote area and separate of this area too difficult to came there which are the boundaries between South Sulawesi and Middle Sulawesi, Objectives: To know mother and child health welfare program especially coverage for fragnance to get Tetanus Toxoid Immunization, as well as minimum health services standard. Method: to be action of this study used Rapid Survey Method, and the data processing using Epi6 Version Windows. Result: The result of this study can be prepare health information from secondary data (Integrated Recording and Reporting System) and primary data from this study which describing 1) pregnancy inspection and contact with manpower of health (midwife, nurse and doctor) 2) coverage Tetanus Toxoid Immunization and 3) Tetanus Toxoid Immunization frequencies Conclusion: The conclude of this study which are the reporting from secondary data (Integrated Recording and Reporting System) give some information about community health as basic health services facilities, but data from the study describing some information about situation and condition community health in the field.